A Review of the Literature on Community Resilience - Crespo, Julio E.; Lirios, Cruz García; Sánchez, Arturo Sánchez (Journal of Ecohumanism, 2024)
The environmental complexity of a specific area has been examined using a model that anticipates the emergence of two identities: entropic and negentropic. In situations of risk, scarcity, and adverse conditions, communities come together to mitigate the impact of natural disasters on community health. Our main objective is to establish a model for examining stress and community resilience in the context of environmental risk events and natural disasters. This objective drives our research and highlights its significance as it draws from environmental science, disaster management, and community resilience. We conducted a non-experimental, cross-sectional, and exploratory study with a non-probabilistic sample of 600 individuals affected by the flooding of a river in central Mexico. Men and women significantly differed in risk, stress, and resilience levels. This helped to establish the model of dependency relationships between the variables that explain isomorphic environmental complexity. Our study suggests that by including certain variables, we can illustrate the logical trajectories of proposed dependency relationships, with significant practical implications for understanding and managing community resilience in the face of environmental risk events and natural disasters.